The singlet excited state of BODIPY promoted aerobic cross-dehydrogenative-coupling reactions under visible light. Issue 56 (17th June 2015) - Wang, Xu-Zhe; Meng, Qing-Yuan; Zhong, Jian-Ji; Gao, Xue-Wang; Lei, Tao; Zhao, Lei-Min; Li, Zhi-Jun; Chen, Bin; Tung, Chen-Ho; Wu, Li-Zhu
Abstract : We disclose for the first time that the singlet excited state ( 1 PS*) of BODIPY rather than triplet excited state ( 3 PS*) can drive C–H bond activation to form C–C and C–P bonds smoothly upon irradiation by visible light. Abstract : In contrast to previous studies, we disclose for the first time that the singlet excited state ( 1 PS*) of BODIPY rather than the triplet excited state ( 3 PS*) can drive C–H bond activation to form C–C and C–P bonds smoothly, which offers new methods to promote organic transformation under visible light irradiation.